Modulating the dose-rate differently affects the responsiveness of human epithelial prostate- and mesenchymal rhabdomyosarcoma-cancer cell line to radiation. (2nd June 2020) - Petragnano, Francesco; Pietrantoni, Ilaria; Di Nisio, Valentina; Fasciani, Irene; Del Fattore, Andrea; Capalbo, Carlo; Cheleschi, Sara; Tini, Paolo; Orelli, Simone; Codenotti, Silvia; Mazzei, Maria Antonietta; D'Ermo, Giuseppe; et al.
Abstract: Purpose: Radiation therapy (RT), by using ionizing radiation (IR), destroys cancer cells inducing DNA damage. Despite several studies are continuously performed to identify the best curative dose of IR, the role of dose-rate, IR delivered per unit of time, on tumor control is still largely unknown. Materials and methods: Rhabdomyosarcoma (RMS) and prostate cancer (PCa) cell lines were irradiated with 2 or 10 Gy delivered at dose-rates of 1.5, 2.5, 5.5 and 10.1 Gy/min. Cell-survival rate and cell cycle distribution were evaluated by clonogenic assays and flow cytometry, respectively. The production of reactive oxygen species (ROS) was detected by cytometry. Quantitative polymerase chain reaction assessed the expression of anti-oxidant-related factors including NRF2, SODs, CAT and GPx4 and miRNAs (miR-22, -126, -210, -375, -146a, -34a). Annexin V and caspase-8, -9 and -3 activity were assessed to characterize cell death. Senescence was determined by assessing β-galactosidase (SA-β-gal) activity. Immunoblotting was performed to assess the expression/activation of: i) phosphorylated H2AX (γ-H2AX), markers of DNA double strand breaks (DSBs); ii) p19 Kip1/Cip1, p21 Waf1/Cip1 and p27 Kip1/Cip1, senescence-related-markers; iii) p62, LC3-I and LC3-II, regulators of autophagy; iv) ATM, RAD51, DNA-PKcs, Ku70 and Ku80, mediators of DSBs repair. Results: Low dose-rate (LDR) more efficiently induced apoptosis and senescence in RMS while high dose-rate (HDR) necrosis in PCa. This paralleled with a lower ability of LDR-RMS and HDR-PCa irradiated cells to activate DSBs repair. Modulating the dose rate did not differently affect the anti-oxidant ability of cancer cells. Conclusion: The present results indicate that a stronger cytotoxic effect was induced by modulating the dose-rate in a cancer cell-dependent manner, this suggesting that choose the dose-rate based on the individual patient's tumor characteristics could be strategic for effective RT exposures.